Inclusion of Individuals with Special Educational Needs to the Education Environment of Institutions of Vocational (Technical and Vocational) Education: the Experience of Developed Countries and the Situation in Ukraine - Liesnikova М. V. (Statistics of Ukraine, 2022)
The process of inclusion involves the comprehensive involvement of students with special educational needs in the educational environment of a vocational (technical and vocational) education institution (hereinafter – V(VT)E), which is the basis of inclusive educational environment. Developed countries, in particular the countries of the European Union, make a lot of efforts to create an inclusive educational environment in P(VT)E institutions. Individuals with special educational needs (hereinafter – SEN) are fully included in the educational environment of P(VT)E institutions in the EU countries. For all institutions, a single educational program for obtaining P(VT)E is used, with the possibility of its individualization for students with SEN. In the vast majority of the considered countries, special support programs for applicants with SEN are operating. All individuals with SEN, according to individual needs, study in main (ordinary) V(VT)E institutions, in specialized V(VT)E units as part of the main institution, and in specialized V(VT)E institutions. An individual educational program is drawn up for each applicant with the SEN, which contains detailed information about the qualifications that such a person must acquire, an individual educational plan, the necessary teaching aids, preparatory and rehabilitation instruction and instructions, as well as a list of social services provided to the applicant(s) during studies. In Ukraine, students with SEN study in mixed inclusive groups in regular V(VT)E institutions according to specially developed educational programs. A team of psychological and pedagogical support works in the V(VT)E institution to support such individuals. Currently, there are active processes of inclusion of students with SEN in the educational environment of the V(VT)E institution. The pedagogical community believes that students with SEN, regardless of age, can master any skills of their choice, and does not agree that a student who misbehaves should be excluded from the V(VT)E institution. At the same time, there is a problem with the accessibility of V(VT)E institutions, because not all institutions are adapted to the visit of students with special needs. In order to improve the existing situation and achieve comprehensive inclusion of the SEN axis in the educational environment of V(VT)E institutions, it is necessary to: update morally outdated educational equipment; updating the content of educational programs in accordance with the individual needs of each applicant; increasing the level of popularization of V(VT)E among school-aged youth; expanding access to special teachers (for example, a sign language interpreter, a typhologist, a special education teacher, a psychologist); expansion of architectural accessibility of V(VT)E institutions; development of visual and practical teaching aids and educational literature for students with SEN.